Program Bangkit 2023 Persiapan Karir Gratis Untuk Mahasiswa - Ridwan Hidayat; Sandika Galih (Journal of Information Systems and Management (JISMA), 2024)
this 2023 rising program is a free program specifically for undergraduate or D4 students starting from semester 5 and above and D3 students starting from semester 3 and above rising 2023 this is a career readiness program affiliated with the independent campus in a certified independent study program and will take place fully online in even semesters or from January to July 2023. This awakening program is here with the aim of preparing high-caliber digital talent through technology training, soft skills training, and also English so that later the graduates will be ready for a career in the world of IT and this program in English with material specially designed by Google and supported by Goto, Traveloka, and also Diptek, this year the revival program has entered its 4th year and has produced more than 5000 reliable graduates from all over Indonesia with the competencies and skills needed by industry There are many benefits that can be obtained when participating in this awakening program, some of which have Industry Standards. Then there are three learning paths that can be chosen according to the interests chosen, namely machine learning, mobile development, and cloud computing, not only technical skills. Later, you will learn English and soft skills that you can use in the world of work.